2020
DOI: 10.1155/2020/7802560
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Malaria and Its Associated Factors at Issaka Gazobi Maternity of Niamey in Niger

Abstract: Background. Congenital malaria is a serious and common infection in tropical Africa. It has multiple consequences on the newborn and the mother. Objective. The objective of this study is to calculate the prevalence of congenital malaria, describe its clinical signs, and analyze its associated factors. Methodology. It is a cross-sectional and prospective study, conducted at Issaka Gazobi Maternity of Niamey, from June 1 to November 30, 2017. The diagnosis was made by microscopy of a thick and thin blood smear o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
4
2
Order By: Relevance
“…The CM was statistically higher in newborn whose mothers had malaria in the last year, gestational and placental malaria, although only placental malaria was significant in the multivariate adjustment. These findings differ from previous studies that have documented other factors associated with CM such as low birth weight, anemia, preterm delivery [7], maternal parasitaemia, pregnancies, maternal age [9,11], maternal hemoglobin level [11], and use of mosquito net [10]. In this sense, the current study only agrees with the research of Hangi et al, who reported the association with placental malaria [9].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The CM was statistically higher in newborn whose mothers had malaria in the last year, gestational and placental malaria, although only placental malaria was significant in the multivariate adjustment. These findings differ from previous studies that have documented other factors associated with CM such as low birth weight, anemia, preterm delivery [7], maternal parasitaemia, pregnancies, maternal age [9,11], maternal hemoglobin level [11], and use of mosquito net [10]. In this sense, the current study only agrees with the research of Hangi et al, who reported the association with placental malaria [9].…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, a frequency of 12.2% (95%CI = 9.4-14.9) was found, which is lower than those reported in studies from Africa that used a similar case definition, that is, positive by TBS or PCR in peripheral or cord blood samples, in which prevalences between 18.6% and 56.8% were reported [7,11]. It is also totally different from studies that evaluated both blood samples with TBS, which reported frequencies of 6.1% [9] and 26.5% [10], and also from the figures of a meta-analysis in which no cases were reported for the Colombian studies (although this figure of 0.0 is consistent with the TBS results of the current study) [13]. This contrast in figures accounts for Colombia's epidemiological and parasitological peculiarities that, despite not Compared to Colombian studies that tested umbilical cord samples with TBS, the current data are the same as other two previous studies that did not find cases with this test [17,19], and are lower than the first investigations in the country about CM that registered frequencies of 2.7% [14], 2.4% [16] and 1.8% [15].…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…This can happen if the mother experiences malaria symptoms during pregnancy, but it can also occur in cases where the mother is asymptomatic, making it difficult to diagnose both in the mother and the newborn. 1,2 It is a rare but serious condition that can result in significant morbidity and mortality in neonates. 1 Plasmodium falciparum is the most prevalent species involved in congenital malaria; however, Plasmodium vivax and Plasmodium malariae can also be involved.…”
Section: Introductionmentioning
confidence: 99%